Estimating Cecidomyiidae (Diptera) species richness in Finland using DNA barcoding - Kiljunen, Niina (2022)
Cecidomyiidae is a hyperdiverse but inadequately studied dipteran family. The number of described Cecidomyiidae species in the world is 6600 but the true species count is still regarded as unknown. Based on DNA barcodes, the number of Cecidomyiidae species in the world is estimated to be as high as 1.8 million. In Finland, no thorough inventories of Cecidomyiidae have been conducted, and the known species count is 384. The purpose of this study was to estimate the expected number of Cecidomyiidae species occurring in Finland utilising BINs (Barcode Index Number) for preliminary species delimitation. Cecidomyiids were collected from eight sites across the country using Malaise traps in the summer of 2020. Supplementary material from 13 sites was also included to the study. The barcode fragment of the COI (cytochrome oxidase c subunit I) gene was sequenced from 9025 Cecidomyiidae specimens. Of the analysed specimens, 7838 recovered validated sequences and were assigned to 1420 BINs. Species count was estimated using model-based extrapolations from rarefaction curves of the abundance data. Whole material is estimated to contain 1.8-fold species count compared to the analysed proportion (⅓). Since further extrapolated rarefaction curve did not reach an asymptote, the estimate of the number of Cecidomyiidae species in Finland still remains largely unknown. However, Finnish Cecidomyiidae fauna evidently consist of thousands of species. The result is congruent with previous studies and points out the efficiency of DNA based methods in dark taxa research.